(3QSGdI ehVhYI ddaQGSI heYQaI GdNjds - (3GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOj, ef Hfj Bcd GdeQGQ , J (B80 (3b g`s
(3ChdgG (B:s
(3CeG HYO agPg QSGdI ehVhYI ddaQGSI heYQaI GdNjd s
(3BNQgG (B:s
(3hEPG cGf HGdaQS GdUaQG Gddhf QCSgG ZdjX hBPGfgG WhGd dGJQcHgG hdGJbQHgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B351s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs